2017
DOI: 10.1021/acs.jafc.7b02487
|View full text |Cite
|
Sign up to set email alerts
|

Zein Nanoparticles Uptake and Translocation in Hydroponically Grown Sugar Cane Plants

Abstract: The main objective of this study was to investigate the uptake and translocation of positively charged zein nanoparticles (ZNPs) in hydroponically grown sugar cane plants. Fluorescent ZNPs (spherical and measuring an average diameter 135 ± 3 nm) were synthesized by emulsion-diffusion method from FITC-tagged zein. Fluorescent measurement following digestion of plant tissue indicated that sugar cane roots had a significant adhesion of ZNPs, 342.5 ± 24.2 μg NPs/mg of dry matter, while sugar cane leaves contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 42 publications
(64 reference statements)
0
53
0
Order By: Relevance
“…Prasad et al . 32 reported that zein nanoparticles were internalized by the roots and were transported to different plant organs. Since such nanoparticles can penetrate the plant tissue, they may be transported within the roots by apoplastic and symplastic pathways, which are involved in the uptake of water and nutrients 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Prasad et al . 32 reported that zein nanoparticles were internalized by the roots and were transported to different plant organs. Since such nanoparticles can penetrate the plant tissue, they may be transported within the roots by apoplastic and symplastic pathways, which are involved in the uptake of water and nutrients 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it may be hypothesized that nanoencapsulation could directly favor the plant‐atrazine interaction, allowing more efficient root uptake and xylem translocation of the herbicide in the shoots, where the herbicide will act. Studies have shown that some polymeric and lipid nanoparticles can be absorbed by roots or leaves, allowing their distribution throughout the plant . Assays monitoring fluorescence‐labeled nanocapsules and atrazine levels in different plant tissues are underway to unveil the mechanisms of action of nanoatrazine in pre‐emergence treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some polymeric and lipid nanoparticles can be absorbed by roots or leaves, allowing their distribution throughout the plant. [37][38][39] Assays monitoring fluorescence-labeled nanocapsules and atrazine levels in different plant tissues are underway to unveil the mechanisms of action of nanoatrazine in pre-emergence treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that the NPs can easily penetrate the cell wall to release the proteins in situ , which facilitates protein–receptor interactions. Several previous reports revealed that some NPs can enter plant tissue through foliar stoma or root absorption …”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports revealed that some NPs can enter plant tissue through foliar stoma or root absorption. [32][33][34][35] The wheat seeds treated with P@NPs showed positive effects on seed vigor index [ Fig. 3(b)].…”
Section: Discussionmentioning
confidence: 99%